2020
DOI: 10.15252/embj.2019102363
|View full text |Cite
|
Sign up to set email alerts
|

Rotational motion and rheotaxis of human sperm do not require functional CatSper channels and transmembrane Ca 2+ signaling

Abstract: Navigation of sperm in fluid flow, called rheotaxis, provides long‐range guidance in the mammalian oviduct. The rotation of sperm around their longitudinal axis (rolling) promotes rheotaxis. Whether sperm rolling and rheotaxis require calcium (Ca2+) influx via the sperm‐specific Ca2+ channel CatSper, or rather represent passive biomechanical and hydrodynamic processes, has remained controversial. Here, we study the swimming behavior of sperm from healthy donors and from infertile patients that lack functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 70 publications
(147 reference statements)
7
53
0
2
Order By: Relevance
“…Whether exposure of the human sperm cells, either within the male or female reproductive tract, to environmental chemicals acting on CatSper can interfere with the fertilization process remains to be shown. However, the fact that impaired progesterone-signaling is associated with reduced male fertility (14)(15)(16)(17)(18)(19)(20) and that men who lack functional CatSper are completely infertile (18,(21)(22)(23)(24)(25)(26)(27)(28)(29) hints that environmental chemicals interfering with this signaling pathway could make it more difficult for the human sperm cells to successfully locate and fertilize the oocyte. As our experiments have been performed on sperm cells in vitro future studies would be needed to validate our results and to examine the effects of exposure to bisphenols on fertility in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether exposure of the human sperm cells, either within the male or female reproductive tract, to environmental chemicals acting on CatSper can interfere with the fertilization process remains to be shown. However, the fact that impaired progesterone-signaling is associated with reduced male fertility (14)(15)(16)(17)(18)(19)(20) and that men who lack functional CatSper are completely infertile (18,(21)(22)(23)(24)(25)(26)(27)(28)(29) hints that environmental chemicals interfering with this signaling pathway could make it more difficult for the human sperm cells to successfully locate and fertilize the oocyte. As our experiments have been performed on sperm cells in vitro future studies would be needed to validate our results and to examine the effects of exposure to bisphenols on fertility in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of CatSper by progesterone controls important sperm functions (13). A suboptimal progesterone-induced Ca 2+ influx is associated with reduced male fertility (14)(15)(16)(17)(18)(19)(20) and men who lack functional CatSper are sterile (18,(21)(22)(23)(24)(25)(26)(27)(28)(29), illustrating the importance of CatSper and Ca 2+ signaling for normal male fertility. Studies have shown that human CatSper can be promiscuously activated by various signaling molecules (30), steroids (31,32), small molecules (33), and environmental chemicals (34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…The CatSper channel (cation channel of sperm) represents the principal pathway for Ca 2+ entry into the flagellum of sperm from many species (1)(2)(3)(4)(5)(6)(7). The activity of CatSper is controlled by both the membrane potential (V m ) and intracellular pH (pH i ) (2)(3)(4)6,8,9), and, in human sperm, also by oviductal steroids and prostaglandins (3,4,(10)(11)(12)(13)(14). Thereby, CatSper translates changes of the chemical microenvironment into changes of [Ca 2+ ] i and swimming behavior, which enables sperm to reach the site of fertilization, to overcome the egg´s protective vestments, and, ultimately, to fertilize the egg (1,(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of CatSper is controlled by both the membrane potential (V m ) and intracellular pH (pH i ) (2)(3)(4)6,8,9), and, in human sperm, also by oviductal steroids and prostaglandins (3,4,(10)(11)(12)(13)(14). Thereby, CatSper translates changes of the chemical microenvironment into changes of [Ca 2+ ] i and swimming behavior, which enables sperm to reach the site of fertilization, to overcome the egg´s protective vestments, and, ultimately, to fertilize the egg (1,(14)(15)(16)(17)(18)(19)(20). CatSper is, hence, absolutely required for fertilization in mice and humans (1,11,13,14,(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a recent study by Wilińsky et al [112] showed only temporal negative influence of H 2 S on sperm chemotaxis, probably due to motility inhibition. The specific mechanism and extent of involvement of the CatSper channels in the previously mentioned processes is still a matter of debate [113,114]. In addition, the opening of K + channels induces membrane hyperpolarization, representing the predominant process during capacitation.…”
Section: No and H 2 S Interactionsmentioning
confidence: 99%